The Effect of Moisture Content on Reducing the Free Fatty Acid Content of Nyamplung Seed Oil (Callophylum inophyllum) Using Factorial Design Method - Pambayun, Faizal; Broto, R. T. D. Wisnu (Journal of Vocational Studies on Applied Research, 2023)
Nyamplung seeds (Calophyllum inophyllum) have an oil content of 50–70%, in Indonesia nyamplung seeds have a high productivity of 20 t/ha. The process of extracting nyamplung seed oil chemical process produces a higher yield than mechanical. Extraction was collected using the soxhletation extraction method because the oil can be extracted perfectly and requires little solvent. The FFA content is very high, ranging from 15-30% which causes high oil quality to decrease. The high FFA content is due to the high % water content (23-25%) in nyamplung seeds, which causes a hydrolysis process where triglycerides dissociate in the presence of water, glycerol and FFA. The research variables are the moisture content of nyamplung seeds (8% and 12%), the size of the material (15 and 25 mesh), and the ratio of the material to the solvent (1:4 and 1:6) using the factorial design method for research optimization using variable moisture content Nyamplung seed is 8%, size is 20 mesh, and raw material to solvent ratio is 1:5. Novelty value research is effect of % water content on reduction of free fatty acid(FFA) levels contained nyamplung seed oil. Whereas in previous research Adenuga et al., (2021) % water content was not the main parameter for reducing free fatty acid levels. But the main parameters are only drying temperature and oven temperature. FFA content without reducing the % water content of 24 mg KOH/g Jahirul et al. (2015) and 29.2 mg KOH/g Hasibuan et al. (2013) whereas the results of the study showed an FFA level of 13.30%, which means that there was a decrease in FFA levels directly proportional to the decrease in the moisture content of nyamplung seeds.